RAS, ETNISITAS, DAN IDENTITAS DALAM NOVEL BATAS LANGIT KARYA MOHAMED LATIFF MOHAMED - Mustofa, Ali (ATAVISME, 2008)
This article describes the issues of post-colonialism in one of contemporary Singaporean literatures Batas langit by Mohamed Latiff Mohamed: Post-colonial issues explored in the present paper are race, ethnicity, and identity. Latiff has successfully obscured his views about Malay people and their culture. His views are somewhat skeptical and pessimistic. However, Latiff has been successfully transforming the existentialism views into his works, and has made him one of the great authors of Singapore.